New Mothers' Experiences with Online Postpartum Forums. Issue 1 (January 2019) - Teaford, Dominique; McNiesh, Susan; Goyal, Deepika
Abstract: Purpose: To explore women's experiences with an online forum during the postpartum period. Study Design and Methods: All women involved in an online postpartum "birth club" onBabycenter.com during the first 6 months postpartum were invited to participate in the study. Participant characteristics and baseline mental well-being data were obtained along with their response to three open-ended questions about their experiences participating in an online mothers group. Descriptive statistics and qualitative content analysis were used to analyze data. Results: Women ( N = 393) who responded to open-ended questions were 29.2 (SD = 5.3) years old, Caucasian (85%), married or in a committed relationship (81%), and lived in the United States (75%). Ninety percent ( n = 354) completed the Edinburgh Postnatal Depression Screening Scale, of whom 18% ( n = 65) scored ≥13, indicating risk of developing postpartum depression. Data analysis revealed five themes. The themes were integrated under the holistic concept of community and included 1) social support; 2) anonymity; 3) in-groups; 4) drama; and 5) entertainment/pastime. Clinical Implications: Findings suggest online forums can provide social support for new mothers. They can facilitate sharing of information, act as a source of entertainment, and provide a sense of community for participants who might otherwise feel isolated due to the demands of new motherhood. Nurses working with childbearing women should be aware of the positive and negative aspects of online forums so they can support new mothers who choose to participate. Abstract : Most new mothers use the Internet. An on-line forum for new mothers can offer peer support, especially in the first few months at home with the new baby. In this study, new mothers describe their experiences with on-line support during the first six months postpartum.